2012
DOI: 10.1186/1471-2105-13-212
|View full text |Cite
|
Sign up to set email alerts
|

Screening of selective histone deacetylase inhibitors by proteochemometric modeling

Abstract: BackgroundHistone deacetylase (HDAC) is a novel target for the treatment of cancer and it can be classified into three classes, i.e., classes I, II, and IV. The inhibitors selectively targeting individual HDAC have been proved to be the better candidate antitumor drugs. To screen selective HDAC inhibitors, several proteochemometric (PCM) models based on different combinations of three kinds of protein descriptors, two kinds of ligand descriptors and multiplication cross-terms were constructed in our study.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
0
25
1
Order By: Relevance
“…Nonetheless, in the case of the dengue virus NS3 proteases dataset, although NP kernel produces a statistically correct modeling with RMSEP ext and R01emitalicext2 values of 0.48 and 0.91, it is slightly outperformed by the Bessel kernel, which displays respective RMSEP ext and R01emitalicext2 values of 0.44 and 0.92 (Table 2). The PUK kernel [65] exhibited strong mapping power in previous studies of HIV-1 proteases and histone deacetylases (HDAC) inhibitors, [63,64] but in the present study we could not obtain satisfactory models for none of the three datasets. The Laplacian and Bessel kernels allow a proper mapping of the three datasets with R01emitalicext2 values within the range 0.60–0.90 (see Table 2 for further details).…”
Section: Resultscontrasting
confidence: 60%
“…Nonetheless, in the case of the dengue virus NS3 proteases dataset, although NP kernel produces a statistically correct modeling with RMSEP ext and R01emitalicext2 values of 0.48 and 0.91, it is slightly outperformed by the Bessel kernel, which displays respective RMSEP ext and R01emitalicext2 values of 0.44 and 0.92 (Table 2). The PUK kernel [65] exhibited strong mapping power in previous studies of HIV-1 proteases and histone deacetylases (HDAC) inhibitors, [63,64] but in the present study we could not obtain satisfactory models for none of the three datasets. The Laplacian and Bessel kernels allow a proper mapping of the three datasets with R01emitalicext2 values within the range 0.60–0.90 (see Table 2 for further details).…”
Section: Resultscontrasting
confidence: 60%
“…An alternative and unbiased approach, mass spectrometry (MS)-based proteomic analysis, is also matured. Except for the advances in experiment, the developments in highperformance calculation techniques have also enhanced our knowledge into microscopic level of the working mechanism (246)(247)(248). The potential power of these methodologies in identifying the channels, as well as post-translational modifications of channel components, is already very clear (243)(244)(245).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has revealed that combinations of descriptors from different aspect may help increase the performance of proteochemometric modeling . PCM has been previously shown to be successful in many protein–ligand interactions studies including melanocortin receptors, G‐protein coupled receptors,, multiple mutated variants of HIV‐1 protease andreverse transcriptase, cytochrome P450,, protein kinases, dengue virus NS3 proteases, histone deacetylases, penicillin‐binding proteins, and carbonic anhydrases ,…”
Section: Introductionmentioning
confidence: 99%